The Necessity of the Digital Economy for Sustainable Economic Growth in OECD Countries - Yapi, Boni David Jonathan; Seraj, Mehdi; Ozdeser, Huseyin (Journal of Economics and Behavioral Studies, 2024)
This paper’s main intent is to study the relationship between the digital economy and the sustainable economic growth of selected OECD countries from 2016 to 2020. In doing so, we will also endeavor to shed a brighter light on distinct elements of the digital economy and to comprehend their collective inputs on the economic returns of the digital systems. To achieve this, secondary data have been gathered to contribute to the quantitative design research method. We further employed a panel data set and regression techniques such as the unit root test, the cointegration test and the dynamic GMM amongst others. The results of the study revealed that sustainable economic growth is slightly significantly linked to the input of the digital economy in the short and long run. However, it has also been discovered that e-commerce revenues have a significantly positive effect on sustainable economic growth in the short and long run. Lastly, this study recommended the establishment of national and international economic metrics, reflecting more on the presence of digital systems.